2014
DOI: 10.1080/24748668.2014.11868751
|View full text |Cite
|
Sign up to set email alerts
|

Effects of technique, age and player’s role on serve and attack efficacy in high level beach volleyball players

Abstract: The aim of the present study was to assess effects of technique of execution, age and player's role on serve and attack efficacy. A total of 1.100 sen'es and 1.165 attacks from under-19, 927 serves and 1.015 attacks from umler-21, and 1.564 serves and 1.854 attacks from senior were assessed through video match analysis. Techniques considered for serve were standing serve (SS), jump serve (JS) and float jump serve (FJS),and for attacks were spike and shot. All players were analysed according to their role (defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 19 publications
1
19
0
4
Order By: Relevance
“…This data can be related to the game dimensions assigned to an individual space of play per player of 32 m. These data suggest that beach volleyball is a sport based on explosive actions of anaerobic alactic type. The serve is a positive performance indicator of winning teams (Zetou et al, 2006;Medeiros et al, 2014Medeiros et al, , 2017. The results showed significant gendered differences in the effectiveness of the serve.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This data can be related to the game dimensions assigned to an individual space of play per player of 32 m. These data suggest that beach volleyball is a sport based on explosive actions of anaerobic alactic type. The serve is a positive performance indicator of winning teams (Zetou et al, 2006;Medeiros et al, 2014Medeiros et al, , 2017. The results showed significant gendered differences in the effectiveness of the serve.…”
Section: Discussionmentioning
confidence: 91%
“…In men, effectiveness decreases when players serve in motion and using more power. Thus, male players favor a float jump serve given that it causes difficulty for opponents through ball oscillation (Buscà et al, 2012;Medeiros et al, 2014). The results show that the jump serve is the one with the highest percentage of errors and produces the fewest aces, thus being in line with Laios (2008) in terms of errors but not in terms of aces.…”
Section: Discussionmentioning
confidence: 93%
“…Challoumas and Artemiou emphasized the importance of the score taken by the attack upon winning the match, and expressed that the studies to be carried upon developing vertical leaping and attack technique would improve the attack performance (Challoumas & Artemiou, 2018). Medeiros, Mesquita, Marcelino & Palao stated that attack efficiency was highly relational with the technique and age (Medeiros, Mesquita, Marcelino, & Palao, 2014). Nikos and Elissavet reported that the number of score from the attack increased as the efficiency of the setter increased (Nikos & Elissavet, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Medeiros ve arkadaşları, servis ve atak etkinliğinin oyuncunun mevkisi, yaşı ile ilişkili olabileceğini vurgulamışlardır (Medeiros, Mesquita, Marcelino, & Palao, 2014).…”
Section: Discussionunclassified